Global loss of Tfr2 with concomitant induced iron deficiency greatly ameliorates the phenotype of a murine thalassemia intermedia model. Issue 2 (27th November 2020) - Schmidt, Paul J.; Fitzgerald, Kevin; Butler, James S.; Fleming, Mark D.
Abstract: β‐thalassemias result from mutations in β‐globin, causing ineffective erythropoiesis and secondary iron overload due to inappropriately low levels of the iron regulatory hormone hepcidin. Mutations in transferrin receptor 2 (TFR2) lead to hereditary hemochromatosis (HH) as a result of inappropriately increased iron uptake from the diet, also due to improperly regulated hepcidin. TFR2 is also thought to be required for efficient erythropoiesis through its interaction with the erythropoietin receptor in erythroid progenitors. Transmembrane serine protease 6 (TMPRSS6), a membrane serine protease expressed selectively in the liver, participates in regulating hepcidin production in response to iron stores by cleaving hemojuvelin (HJV). We have previously demonstrated that inhibiting TMPRSS6 expression with a hepatocyte‐specific siRNA formulation, induces hepcidin, mitigates anemia, and reduces iron overload in murine models of β‐thalassemia intermedia and HH. Here, we demonstrate that Tmprss6 siRNA treatment of double mutant Tfr2 Y245X/Y245X HH Hbb th3/+ thalassemic mice induces hepcidin and diminishes tissue and serum iron levels. Importantly, treated double mutant animals produce more mature red blood cells and have a nearly 50% increase in hemoglobin compared to untreated β‐thalassemic mice. Furthermore, we also show that treatment of Tfr2 Y245X/Y245X HH mice leads to increased hepcidin expression and reduced total body iron burden. These data indicate that siRNA suppression of Tmprss6, in conjunction with the targeting of TFR2, may be superior to inhibiting Tmprss6 alone in the treatment of the anemia and secondary iron loading in β‐thalassemia intermedia and may be useful as a method of suppressing the primary iron overload in TFR2‐related (type 3) hereditary hemochromatosis.